The Use of ICT in Teaching English at Eleventh Grade of Kalam Kudus Senior High School Malang - Sitti Aisyah (Graduate Program, University of Islam Malang, 2019)
Nowadays, most of institution has equipped by complete facilities and infrastructure such as complete multimedia classroom. The education system that applies in Indonesia requires schools to fulfill this phenomenon especially in language teaching learning.The objective of the study was to examine and investigate an English Teacher of Senior High School Christian Kalam Kudus efforts on how the teaching learning process could improve through the use of ICT. By these current issue the researcher interested to conduct a case study under following research questions: How do the Eleventh English teacher of Senior High School Christian Kalam Kudus apply the technology in the teaching learning process across proficiency level in the classroom? What type of ICT approach that the teacher uses during learning teaching process in the classroom? To what extend the teacher use ICT in English language teaching?A descriptive research methodology was applied in this study. Carried out an English teacher of Senior High School Christian Kalam Kudus Malang. In which the teacher teaches 3 of eleventh grade classes consist of 22-24 of students in each class. The data was collected through interview in 22 questions and 16 meeting of observation. The result shows that how teacher could optimize the use of ICT by some of application in the internet in which to increase his teaching learning process. The innovations carried out by teachers by using smartphones that are owned by students to access several applications through internet. Furthermore, the creativity made by the teacher from traditional learning, textbooks, became ICT-based by using applications on the internet intended to make learning in his class interesting and enjoyable. Lastly is the process of motivating students in the learning process in class by creating an effective learning environment through ICT learning mediaAt the end of study researcher found that how the utilizing of ICT in teaching English have the massive changes in students learning progress. It increased both teacher method in teaching English and the students’ achievement in English.Keywords: ICT Approach, Teaching English, Proficiency Level